2001
DOI: 10.1046/j.1468-3148.2001.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Four Therapy Procedures on Communication in People with Profound Intellectual Disabilities

Abstract: A number of alternative therapies have recently been employed with people who have intellectual disabilities (IDs). The present study examines the effects of four frequently used therapies on the communication of people with profound ID. Communication was assessed using five measures of positive communication and five measures of negative communication. The therapies assessed were Snoezelen, active therapy, relaxation and aromatherapy/hand massage. There were eight participants in the present study and each re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…However, all of these studies lacked control conditions, and used non-blind measurement or retrospective data collection. Lindsay et al (1997Lindsay et al ( , 2001 in the study already described above found that although there were improvements in rated enjoyment and relaxation in the Snoezelen condition, they were no greater than those in the relaxation condition which was considerably less expensive to implement. Meijs-Roos (1990) in a study of six individuals found no effects from Snoezelen exposure on affective behaviour, stereotypies and other challenging behaviours.…”
Section: Snoezelenmentioning
confidence: 83%
See 1 more Smart Citation
“…However, all of these studies lacked control conditions, and used non-blind measurement or retrospective data collection. Lindsay et al (1997Lindsay et al ( , 2001 in the study already described above found that although there were improvements in rated enjoyment and relaxation in the Snoezelen condition, they were no greater than those in the relaxation condition which was considerably less expensive to implement. Meijs-Roos (1990) in a study of six individuals found no effects from Snoezelen exposure on affective behaviour, stereotypies and other challenging behaviours.…”
Section: Snoezelenmentioning
confidence: 83%
“…For all three participants SIB was effectively reduced by reinforcement methods. Lindsay et al (1997Lindsay et al ( , 2001) conducted a comparison of hand massage, physical therapy, Snoezelen and relaxation therapy with eight subjects using a counter balanced, crossover design. They found that hand massage and active therapy either produced no improvements in a range of measures or were mildly aversive.…”
Section: Sensory Integration Therapymentioning
confidence: 99%
“…), and alternative therapies involving individuals with intellectual disability being guided through physical relaxation, or interacting with sensory and motor stimuli significantly increase levels of positive communication (Lindsay et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Over the past 25 years, only 28 articles have been published regarding the implementation of the CMSE with individuals with intellectual disabilities as found through an intense literature search. Of those 28 articles, only 20 were investigative projects (25)(26)(27)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The number of participants in those research interventions ranged from 1 to 20, averaging at around seven participants per intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various outcome measures were applied. Most publications dealt with challenging behaviors, whereas a handful of articles examined other more functional outcome measures, such as concentration and responsiveness (25,32,35), engagement in a functional task (33) and FOS skills (Foundation Outcome Statement (36)). …”
Section: Introductionmentioning
confidence: 99%